Blocking Sodium‐Taurocholate Cotransporting Polypeptide Stimulates Biliary Cholesterol and Phospholipid Secretion in Mice. Issue 1 (13th August 2019) - Roscam Abbing, Reinout L.P.; Slijepcevic, Davor; Donkers, Joanne M.; Havinga, Rick; Duijst, Suzanne; Paulusma, Coen C.; Kuiper, Johan; Kuipers, Folkert; Groen, Albert K.; Oude Elferink, Ronald P.J.; van de Graaf, Stan F.J.
Abstract : Active secretion of bile salts into the canalicular lumen drives bile formation and promotes biliary cholesterol and phospholipid output. Disrupting hepatic bile salt uptake, by inhibition of sodium‐taurocholate cotransporting polypetide (NTCP; Slc10a1) with Myrcludex B, is expected to limit bile salt flux through the liver and thereby to decrease biliary lipid excretion. Here, we show that Myrcludex B–mediated NTCP inhibition actually causes an increase in biliary cholesterol and phospholipid excretion whereas biliary bile salt output and bile salt composition remains unchanged. Increased lysosomal discharge into bile was excluded as a potential contributor to increased biliary lipid secretion. Induction of cholesterol secretion was not a consequence of increased ATP‐binding cassette subfamily G member 5/8 activity given that NTCP inhibition still promoted cholesterol excretion in Abcg8 −/− mice. Stimulatory effects of NTCP inhibition were maintained in Sr‐b1 −/− mice, eliminating the possibility that the increase in biliary lipids was derived from enhanced uptake of high‐density lipoprotein–derived lipids. NTCP inhibition shifts bile salt uptake, which is generally more periportally restricted, toward pericentral hepatocytes, as was visualized using a fluorescently labeled conjugated bile salt. As a consequence, exposure of the canalicular membrane to bile salts was increased, allowing for more cholesterol and phospholipid molecules to be excreted per bile salt. Conclusion: NTCP inhibition increases biliary lipid secretion, which is independent of alterations in bile salt output, biliary bile salt hydrophobicity, or increased activity of dedicated cholesterol and phospholipid transporters. Instead, NTCP inhibition shifts hepatic bile salt uptake from mainly periportal hepatocytes toward pericentral hepatocytes, thereby increasing exposure of the canalicular membrane to bile salts linking to increased biliary cholesterol secretion. This process provides an additional level of control to biliary cholesterol and phospholipid secretion.